The reminders for dental clinics in the COVID-19 post-pandemic era - Huei-Chu Cheng; Sin-Yen Hsieh; Ya-Ai Cheng; Yueh-Tzu Kao (Journal of Dental Problems and Solutions - Peertechz Publications, 2023)
Introduction: The impacts of COVID-19 are enormous and global-wide. Especially, medical treatment activities have been canceled or postponed to avoid the risk of contracting the virus. To prevent the transmission of the COVID-19, methods including early screening, isolation, mass mask use, etc. were applied during the pandemic. Due to the high percentages of vaccination and public policies, the transmission of COVID-19 is under-control.  Main text: For dental care settings, researchers have proposed guidelines for the highest-risk group of healthcare professionals to mitigate the possibility of COVID-19 transmission. Nowadays, patients are flowing to reschedule dental appointments which have been canceled or postponed during the pandemic because of the proper control of COVID-19 transmission. Some dental clinics take certain steps to ensure the safety of patients as well as the treatment team.  Conclusion: Some reminders are offered to the dental administrator to keep vigilant while providing quality service for the needed patients.